Analysis of operating conditions disinfecting processing grain mass in the electric field of high tension ac - Bereka, O.; Schylcov, A.; Usenko, S. (Energy and Automation, 2015)
The problem of current displacement in the grain mass, as part of operational parameters, the disinfecting treatment in the electric field of high tension AC. Established Mathematical formulas for determining the strength of the field and current density in the grain mass displacement, under the influence of an electric field of high tension and separated from the electrode dielectric plates.